2021
DOI: 10.1186/s12885-021-08313-6
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for predicting preoperative regional lymph nodes metastasis in patients with metaplastic breast cancer: a SEER population-based study

Abstract: Background Metaplastic breast cancer (MBC) is a rare subtype of breast cancer, and generally associated with poor outcomes. Lymph nodes metastasis (LNM) is confirmed as a critical independent prognostic factor and determine the optimal treatment strategies in MBC patients. We aimed to develop and validate a nomogram to predict the possibility of preoperative regional LNM in MBC patients. Methods MBC patients diagnosed between 1990 and 2016 in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Histology of MBC contains eight types after screening, including, metaplastic carcinoma, carcinosarcoma, squamous cell carcinoma, spindle cell carcinoma, sarcomatoid carcinoma, fibromatosis-like metaplastic carcinoma, low-grade adenosquamous carcinoma, and metaplastic carcinoma with chondroid differentiation or osseous differentiation ( Hennessy et al, 2006 ; Zhang et al, 2021 ). When the data were grouped in a 7:3 ratio in this study, not all subtypes were included in the training set, and they were analyzed based on the whole population cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Histology of MBC contains eight types after screening, including, metaplastic carcinoma, carcinosarcoma, squamous cell carcinoma, spindle cell carcinoma, sarcomatoid carcinoma, fibromatosis-like metaplastic carcinoma, low-grade adenosquamous carcinoma, and metaplastic carcinoma with chondroid differentiation or osseous differentiation ( Hennessy et al, 2006 ; Zhang et al, 2021 ). When the data were grouped in a 7:3 ratio in this study, not all subtypes were included in the training set, and they were analyzed based on the whole population cohort.…”
Section: Discussionmentioning
confidence: 99%
“…While nomogram can be used to estimate the distantmetastasis risk by integrating the existing clinicopathological factors, improving diagnostic efficiency, reducing time, and economic cost. [ 21 , 22 ] So it is necessary to establish a simple and sensitive prediction model for distant metastasis in MBC patients. The study established a risk prediction model based on the existing evidence to assess the risk of distant metastasis and screen high-risk groups, so as to guide diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The survival prediction model showed good performance in estimating the prognosis individually. For instance, compared with similar predictive models ( 30 , 31 ), the net benefit of DCA plots in our nomogram was larger, which indicated that the nomogram was a reliable clinical tool for predicting survival.…”
Section: Discussionmentioning
confidence: 75%